Rebusan daun kersen lebih efektif dibandingkan rebusan daun kelor dalam menurunkan kadar gula darah puasa pada pasien diabetes tipe 2. - Tri Murti Sanjayani; Parellangi Parellangi; Lukman Nulhakim (MNJ (Mahakam Nursing Journal), 2023)
Hyperglycemia occurs due to too much sugar intake resulting in blood glucose above normal. Treatment that can reduce blood sugar levels is to consume a decoction of moringa leaves and cherry leaves. This research is a quasi-experimental study with a two group pretest-posttest design from August to October 2022. The population in this study were all Type II DM patients within the working area of ​​the Tanah Kuning Health Center, totaling 245 people. The sampling technique in this study was based on Roscoe's theory, so a sample of 30 respondents. The statistical test used is the paired t test if t count (pvalue) <0.05 is obtained, then the hypothesis Ha is accepted and Ho is rejected. The effect of moringa leaf decoction to lower blood sugar levels in Type II DM patients with a value of 0.00 and the effect of cherry leaf decoction to lower blood sugar levels in Type II DM patients obtained a value of 0.00. So there is an effect of moringa leaf decoction and cherry leaf decoction to reduce blood sugar levels in Type II DM patients in the Working Area of ​​the Tanah Kuning Health Center. Keywords: Diabetes Mellitus, Moringa, Kersen.